Sulawesi Sedimentology Literature: A Brief Review - J.T. van Gorsel (Ikatan Ahli Geologi Indonesia, 2011)
Sulawesi is well known for its complex Cretaceous-Tertiary collisional tectonic history, with a succession of volcanic arc deposits. Numerous publications have appeared on these topics. Also quite a few papers discuss general stratigraphy of areas, but very few papers can be characterized as 'sedimentology papers', i.e. papers documenting and interpreting sedimentary structures, measured sections, current directions, provenance, depositional environments, paleogeography, etc.